A mixed integer bi-level DEA model for bank branch performance evaluation by Stackelberg approach - Morteza Shafiee; Farhad Hosseinzadeh Lofti; Hilda Saleh; Mehdi Ghaderi (Journal of Industrial Engineering International, 2016)
One of the most complicated decision making problems for managers is the evaluation of bank performance, which involves various criteria. There are many studies about bank efficiency evaluation by network DEA in the literature review. These studies do not focus on multi-level network. Wu (Eur J Oper Res 207:856-864, 2010) proposed a bi-level structure for cost efficiency at the first time. In this model, multi-level programming and cost efficiency were used. He used a nonlinear programming to solve the model. In this paper, we have focused on multi-level structure and proposed a bilevel DEA model. We then used a liner programming to solve ourmodel. In other hand, we significantly improved the way to achieve the optimum solution in comparison with the work by Wu (2010) by converting the NP-hard nonlinear programing into a mixed integer linear programming. This study uses a bilevel programming data envelopment analysis model that embodies internal structure with Stackelberg-game relationships to evaluate the performance of banking chain. The perspective of decentralized decisions is taken in this paper to cope with complex interactions in banking chain.The results derived frombi-level programmingDEA can provide valuable insights and detailed information for managers to help them evaluate the performance of the banking chain as a whole using Stackelberg- game relationships. Finally, thismodel was applied in the Iranian bank to evaluate cost efficiency.
Keywords: 650; Bi-level programming; DEA; Mixed integer programming; Stackelberg equilibrium; Game theory; Decentralized decision making structure; Bank performance evaluation